Plant-based vaccines for prevention of poultry viral diseases: Newcastle disease - Nurzijah, Ika (2025)
Newcastle Disease (ND) is an economically important viral disease in poultry. Although commercial vaccines are available, ND continues to cause disease outbreaks, particularly in low- and middle-income countries where strict biosecurity measures are often not feasible. Therefore, there is an urgent need for a cost-effective approach to develop improved ND vaccines. This study used Agrobacterium tumefaciens-mediated transient expression in Nicotiana benthamiana via pEAQ-HT expression system, with the aim of developing improved plant expressed NDV vaccines. Bioinformatics analysis was also used to support ND vaccine development.